American Purple Gallinule Porphyrula martinica (Aves: Rallidae) feeding biology in the Middle Parana River flood-plain, Argentina (2012)
The article presents feeding biology studies conducted on the American Purple Gallinule Porphyrula martinica, by means of analyzing 13 stomach contents under different levels of taxonomical resolution. The purpose of the research was to determine both trophic diversity by stomach (H) and accumulated trophic diversity, applying the Relative Importance Index (IRI) and estimating trophic niche amplitude according to the Levins index, as well as finding out alimentary efficiency, prey size percentage and intestinal coefficient (Ri). Resultant spectrum was composed by 16 taxonomical entities, 2 vegetable fractions and 14 animal fractions; trophic diversity by stomach (H) ranged between 0,5 and 1,23; accumulated trophic diversity (Hk) was 2,9; IRI values were as follows: Belostoma sp. 1241, Arachnida n.i. 1134, Paspalum repens 704, Polygonum accuminatum 574; seasonal trophic niche amplitude was 0,88 (summer), 0,7 (spring), 0,76 (fall), and 0,8 (winter); alimentary efficiency was 97,6%; prey sizes percentage was 66% for organisms ranging from 0 to 10 mm; and average intestinal coefficient was 2,72. Researchers conclude that Porphyrula martinica is an omnivorous species, basically phytophage.